Opera de artă plastică – un bun ce face parte din domeniul public sau din domeniul privat? - Chirosca Igor; Grosu Mihaela (Revista Institutului Naţional de Justiţie, 2014)
The purpose of this article is to analize some aspects of the works of fi ne arts as a variety of works in general, as well as a variety of goods within the meaning of the Civil Code of the Republic of Moldova. The authors try to demonstrate that the work of fi ne arts is a specifi c good because it is not covered entirely by the classic civil law norms regarding the classifi cation of the goods. As this type of work stands to be a fl exible structure, in some circumstances it appears in the diff erent forms of goods, from public domain or from private domain.